Application of bistable glass-coated microwire for monitoring and measuring the deformations of metal structural members. (28th February 2023) - Al Ali, M.; Platko, P.; Bajzecerova, V.; Kusnir, S.; Kmet, S.; Nalevanko, S.; Spegarova, A.; Galdun, L.; Varga, R.
Highlights: Contactless deformation monitoring based on bistable glass-coated microwire. Ferromagnetic structural members deformation monitoring. Exclusion of unwanted influence of the external magnetic field. The measurement sensitivity can be enhanced down to 6 × 10 -6. Abstract: The paper presents some experimental results related to innovative research focused on contactless strain measurement and the possibility of substituting conventional electrical strain gauges with bistable glass-coated microwires for structural member monitoring. As a part of the aforementioned research, the results of strain measurements performed on samples made of metallic materials with ferromagnetic nature are shown. During the experimental tests, a strain gauge was used to verify and compare the results obtained from the bistable glass-coated microwire, which can be used as a passive element without the requirement of physical connection to the sensing unit. Moreover, an additional examination confirmed the possibility of separating the influence of the parasitic external magnetic field. The results presented in this paper proved that bistable glass-coated microwires could be considered suitable candidates for contactless strain measurements performed on metallic materials with ferromagnetic nature or in a changing magnetic environment.